Tasks and functions of lawer in the administrative process - Chudyk, Nataliia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article deals with legal status of the lawyer in administrative legal proceedings as an independent participant of the administrative legal proceedings that has his tasks, functions and authorities. After analyzing the works of famous researchers it was noted that as a professional defense counsel and legal representative the lawyer can take part in the wide range of financial and procedural relations where he has scope of functions, rights and responsibilities. The functions, rights and responsibilities of the lawyer, the most important of which is protection of rights, liberties and legal interests of people, define his place in legal relations. The article analyzes legal place of the lawyer in administrative legal proceedings in terms of arbitration policies in the public sphere. The definition of legal and administrative legal status is reviewed together with the existing statutory regulations in relation to defense attorneys and the procedure of the execution of the administrative legal proceedings.